“Convergence or National Styles? The Japanese Challenge to the British-Norwegian Hegemony in the Twentieth-Century Whaling Industry” - Basberg, Bjørn L (Global Markets: The Internationalization of the Sea Transport Industries since 1850, 1998)
Keywords: Antarktis; Svend Foyn; fiskeindustri; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi

A century of German interests in modern whaling, 1860s-1960s - Barthelmess, Klaus (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Nordmenn; Sørishavet; Tyskland; hvalfangere; pelagisk hvalfangst; økonomi

Survival against all odds? Shore station whaling at South Georgia in the Pelagic. Era, 1925-1960 - Basberg, Bjørn L (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk; økonomi; økonomisk historie

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvalfangst 1868-1914. Hvalfangst blir en ny vekstnæring - Hodne, Fritz (Norges økonomiske historie 1815-1970, 1981)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalindustri; økonomi

Moderne sydpolsproblemer - Hambro, Edvard (Samtiden, 1973)
Keywords: Antarktis; jus; politikk; økonomi

Hvalfangsten - Gjermoe, Eilif (Aksjekursene i norsk skipsfart, skipsbygging og hvalfangst i mellomkrigstiden, 1964)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; næringsliv; økonomi

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Sandar sparebank gjennom 100 år : utgitt ved hundre års jubileet - Laug, Kristian ([s.n.], 1960)
Keywords: Antarktis; Norge; Sørishavet; Vestfold; hvalfangstindustri; hvalindustri; økonomi

Banken og byen : Sandefjords sparebank 1857-1957 - Groth, Erling (Sandefjords sparebank, 1957)
Keywords: Norge; Sørishavet; Vestfold; byhistorie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalfangstselskapet; hvalindustri; økonomi

Fem hundre år og femti : fra tollsted til ladested : fra badeby til hvalfangst-sentrum : linjer i Sandefjords økonomiske historie gjennem 550 år - Bogen, Hans (Sandefjord handelsstands forening, 1951)
Keywords: Sørishavet; historie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri; økonomi

Sandefjord handelsstands forening 1901-1951. Bilag til Hans Bogens jubileumsbok "Femhundre år - og femti" - Bogen, Hans; Schelbred, Erik W; Bøe, Frithjof; Klungseth, Alf; Schelbred, Oscar C; Sandberg, Finn; Fogstad, Per; Vangstein, Einar; Hoffstad, Arne (Sandefjord handelsstands forening, 1951)
Keywords: Sørishavet; historie; hvalfangere; hvalfangerselskapet; hvalfangstindustri; hvalindustri; økonomi

Del IV: Hvalfangst - fangstnæring - Knudtzon, Hans Thomas (Norsk fiskeri- og fangsthåndbok : saltvannsfiskeriene : ferskvannsfiskeriene : ishavsfangsten : hvalfangsten, 1949)
Keywords: Sørishavet; fiskerier; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstkvoter; hvalfangstregulering; hvalfangstselskaper; hvalindustri; internasjonal; næring; pelagisk; samarbeid; økonomi

Vestfold og hvalfangsten - Bogen, Hans (Årbok for Den norske turistforening, 1947)
Keywords: Sørishavet; historie; hvalfangst; økonomi

Norwegian patents relating to whaling and the whaling industry : a statistical and historical analysis - Johnsen, Arne Odd (A. W. Brøggers Boktrykkeri A/S, 1947)
Keywords: Nordmenn; Norge; Sørishavet; harpuner; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; økonomi

Hvalen som råvarekilde - Thon, Eivind (Råvarene i verdenshandelen : kapitler av deres historie, og kampene om dem, 1946)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalolje; økonomi

Fischerei und Fang - Johnsen, Oscar Albert (Norwegische Wirtschaftsgeschichte, 1939)
Keywords: Sørishavet; hvalfangst; pelagisk; økonomi

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Foran sesongen 1930-1931 : oversikt over norske og utenlandske hvalfangerselskaper, siste fangstsesongs regnskaper - Sveinung, E (E. Sveinung A.S., 1930)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Norske hvalfangstselskaper 1928-1929 - Diesen, Emil (Økonomisk revue, 1929)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Foran sesongen 1929-1930 : oversikt over norske og utenlandske hvalfangerselskaper, siste fangstsesongs regnskaper - Sveinung, E (E. Sveinung A.S., 1929)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Norske skibs- og fangstselskaper 1918. Hvalfangstselskaperne. Supplem. til skibsselskaperne. Dødvegtliste - Diesen, Emil (A/S Økonomisk literatur, 1919)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi

Norske skibs- og fangstselskaper 1917. Hvalfangstselskaperne. Supplem. til skibsselskaperne. Alfabetisk skibsliste. Dødvegt liste - Diesen, Emil (E. Diesen, 1917)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi

Norske skibs- og fangstselskaper. Fangstselskaper, rederifortegnelse og supplementer - Diesen, Emil (Brun, 1916)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næringsliv; pelagisk; økonomi